" EFFECTIVE STRATEGIES TO ENHANCE STUDENTS' READING COMPREHENSION" (Modern education and development, 2024)
This article explores effective strategies to enhance reading comprehension among learners, emphasizing the importance of engagement, vocabulary development, metacognition, differentiation, and technology integration. Supported by insights from educational researchers like John Guthrie, E.D. Hirsch Jr., and Annemarie Palincsar, it highlights evidence-based approaches such as reciprocal teaching, differentiated instruction, and fostering a reading culture. The article underscores the dynamic interplay between readers and texts, advocating for methods that address diverse learning needs and promote lifelong literacy skills.